A nanoparticulate drug-delivery system for glaucocalyxin A: formulation, characterization, increased in vitro, and vivo antitumor activity. (1st September 2016) - Han, Meihua; Li, Zhitao; Guo, Yifei; Zhang, Jian; Wang, Xiangtao
Abstract: Glaucocalyxin A (GLA) is a phytochemical component with multiple pharmacological activities; however, glaucocalyxin A's wider use has been restricted by its poor solubility. In this study, GLA nanosuspensions were prepared with precipitation-combined ultrasonication and were characterized by dynamic light scattering (DLS), transmission electron microscope (TEM), and differential scanning calorimetry (DSC). The GLA nanosuspensions were spherical with a smooth surface and a small size of 143 nm, the drug payload achieved 8.95%, and the maximum GLA concentration reached 1 mg/mL. The lyophilized powders for the GLA nanosuspensions were amorphous and displayed a biphasic drug release pattern with an initial burst release and a consequent sustained release. In contrast to the free drug solution, GLA nanosuspensions showed higher in vitro antitumor activity against HepG2 cells (IC50 value of 1.793 versus 2.884 μg/mL at 24 h, p  < 0.01). Meanwhile, nanosuspensions displayed better anticancer efficacy than free GLA on H22 bearing mice (54.11% versus 36.02% tumor inhibition rate). These results indicate that GLA nanosuspensions have great potential for the treatment of hepatic cancer.